In vivo evaluation of tropism and biodistribution of synthetic and natural adeno-associated viral vectors by next-generation sequencing - D. O. Maksimov; D. A. Naumova; E. A. Astakhova; V. V. Artemev; S. A. Biryukov; I. S. Abramov; A. A. Navoikova; N. V. Rudev; S. G. Feoktistova; O. V. Glazova; O. N. Mityaeva; P. Yu. Volchkov (Биопрепараты: Профилактика, диагностика, лечение)
INTRODUCTION. The creation of synthetic adeno-associated virus (AAV) vectors during gene therapy development is a labour-intensive and expensive process. The optimal solution to minimise the time and costs associated with gene therapy development lies in the improvement of methods aimed at assessing AAV vector biodistribution and transduction efficiency in vivo.AIM. This study aimed to develop a new bioinformatics-based assessment method for synthetic AAV vector libraries to analyse AAV vector biodistribution and transduction efficiency in vivo.MATERIALS AND METHODS. The production of synthetic AAV vectors involved assigning AAV serotype-specific barcodes (12-nucleotide tags flanked at the 5' end with a sequence encoding the green fluorescent reporter protein). Plasmids carrying unique barcodes were propagated in competent Escherichia coli XL10-Gold cells and used to create two AAV libraries: L1 with a viral genome count of 1010 and L2 with a viral genome count of 1011. AAV production involved HEK293T cell transfection. L1 and L2 library vectors were administered to C57Bl/6N mice by intravenous injection. DNA and RNA were isolated from transduced organs for analysis by next-generation sequencing. The obtained data on DNA and RNA barcode quantities in different murine organs were analysed to assess the biodistribution and transduction efficiency of synthetic AAVs. Barcodes were identified by aligning them to the expected sequences and counted. The resulting values were normalised to the quantity of barcodes in the original library.RESULTS. Seven viral constructs based on different AAV serotypes were created as part of two AAV libraries. Six of the AAV serotypes were synthetic (sAAV1, sAAV2, sAAV3, sAAV4, sAAV5, and sAAV6). Sequencing of murine organ samples revealed significant quantities of DNA barcodes from both AAV libraries in all organs except the brain. For the L1 library, RNA barcodes were detected at a sufficient level in 4 organs, including the skeletal muscles, the heart, the liver, and the adrenal glands. For the L2 library, in addition to the listed organs, sufficient RNA-barcode levels were observed in the gonads and the kidneys. According to transduction efficiency analysis based on RNA barcode levels adjusted for DNA barcodes, sAAV5 was considered the most promising variant for gene therapy of liver-related diseases, whereas sAAV2 and sAAV6 were recognised as holding the most promise for adrenal diseases.CONCLUSIONS. The developed bioinformatics-based assessment method for synthetic AAV vector libraries can analyse AAV vector biodistribution and transduction efficiency in the body. The presented approach has the potential for selecting optimal AAV vectors for specific organs and tissues in further gene therapy development.